Association of α-Synuclein with Lipid Vesicles : Stopped-Flow Kinetics of Concerted Binding and Conformational Change - Jovin, Thomas M. (2014)
Alpha-synuclein (AS), a 140aa intrinsically disordered protein, self-associates into oligomeric forms and aggregates into amyloid fibrils in Parkinson's disease. Certain mutations affect these processes and accelerate disease pathogenesis. The physiological roles of AS are a matter of speculation. Membrane binding is undoubtedly involved and the protein acquires α-helical structure in the process (1).We have studied the thermodynamics and kinetics of AS-membrane association utilizing vesicles (SUVs) of differing composition. Functionally neutral single cysteine mutants of AS were labeled with a polarity sensitive excited-state intramolecular proton transfer (ESIPT) probe (MFE). Double cysteine mutants were labeled with a FRET pair (Alexa Fluor488, Alexa Fluor568) at a series of selected positions in the primary sequence. Kinetic studies were conducted by stopped-flow, using 5-20 nM protein concentrations and increasing levels of SUVs (generally 20-200 µM) Signal changes indicative of membrane association were observed: increased intensity and shape change of dual band ESIPT emission, and altered FRET with the Alexa dyes. The analysis revealed a two-step reaction sequence in the time range <10 s. We attribute the first step to binding, and from the dependence on lipid concentration determined the second order rate constants and corresponding spectroscopic parameters. The second concentration independent step (1-10 s range) presumably arises from conformational changes in the protein (α-helix formation) and its accommodation to or perturbation of the lipid microenvironment (ESIPT dye).Accompanying thermodynamic measurements led to estimates of dissociation constants as a function of membrane composition, charge, and shape (SUVs, LUVs). A new experimental protocol (slopes), implemented in a microplate reader, circumvented technical problems usually manifested in titrations of protein with lipid.